Acute Respiratory Distress Syndrome: The Best Ventilator Techniques (Journal of Pharmaceutical Negative Results, 2019)
As our knowledge of the pathophysiology of acute respiratory distress syndrome (ARDS) has grown, so too have the methods for mechanical ventilation in these patients. The provision of lung-protective mechanical ventilation, which gives priority to tidal volume and plateau pressure limitation, is essential to the treatment of afflicted patients. By tailoring target tidal volumes to each patient's unique respiratory mechanics, lung protection can likely be further improved. There is still uncertainty regarding the best process for choosing the ideal positive end-expiratory pressure (PEEP) in ARDS; lung recruitability is one of the important factors to take into account. In ARDS, noninvasive ventilation must be used carefully because an overly high respiratory drive can worsen lung damage; newer delivery methods show promise in treating hypoxemic respiratory failure. Although clinical trials have not shown that airway pressure release ventilation improves survival over traditional ventilation techniques, it does provide an alternate method to optimize lung recruitment and oxygenation. In cases of refractory hypoxemia, high-frequency oscillatory ventilation rescue therapy is a crucial alternative. High-frequency oscillation may help patients with extremely severe hypoxemia, despite its disappointing lack of benefit (and potential harm) in patients with moderate or severe ARDS, which may be caused by lung hyperdistention and right ventricular dysfunction.